The in vitro immunomodulatory effect of extracellular products (ECPs) of Vagococcus fluvialis L21 on European sea bass (Dicentrarchus labrax) leucocytes. Issue 2 (February 2015) - Román, L.; Acosta, F.; Padilla, D.; El Aamri, F.; Bravo, J.; Vega, B.; Rodriguez, E.; Vega, J.; Déniz, S.; Real, F.
Abstract The immune associated genes, interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin 10 (IL-10), tumor necrosis factor-α (TNF-α), ciclo-oxigenase-2 (COX-2), and Mx gene were studied by real-time PCR in head-kidney leucocytes of sea bass after incubation with the extracellular products (ECPs) of the probiotic strain Vagococcus fluvialis L21 and polyinosinic:polycytidylic acid (POLY I:C), at different times (T1.5, T6, T12, T24, T48 and T72). In general, we can observe how pro-inflammatory cytokines IL-1β, TNF-α, IL-6 and COX-2 studied displayed a strong peak after stimulation with 1.5 h of ECPs of V. fluvialis L21, significant differences (P < 0.05) exist with other periods and with the POLY I: C at the same time. Similarly to the case of IL-10 also produced a statistically significant (P < 0.05) peak of expression on leukocytes that were stimulated with the ECPs of V. fluvialis L21. In the case of Mx gene expression, we note that in almost all sampling times there is an up-regulation of the Mx gene in leucocytes incubated with ECPs and POLY I:C compared to the control and Mx expression was higher in leucocytes that were stimulated with the ECPs of V. fluvialis for all times, except in T24. With these results we can consider that the ECPs of V. fluvialis L21 have a great power of stimulating the in vitro expression of immune-related genes and may even be useful as adjuvants for vaccine in aquaculture.